Eighth-Grade Algebra Course Placement and Student Motivation for Mathematics - Rahila Simzar; Thurston Domina; Cathy Tran (SAGE Publishing, 2016)
This study uses student panel data to examine the association between algebra placement and student motivation for mathematics. Changes in achievement goals, expectancy, and task value for students in eighth-grade algebra are compared with those of peers placed in lower-level mathematics courses (N = 3,306). In our sample, students placed in algebra reported an increase in performance-avoidance goals as well as decreases in academic self-efficacy and task value. These relations were attenuated for students who had high mathematics achievement prior to algebra placement. Whereas all students reported an overall decline in performance-approach goals over the course of eighth grade, previously high-achieving students reported an increase in these goals. Lastly, previously high-achieving students reported an increase in mastery goals. These findings suggest that while previously high-achieving students may benefit motivationally from eighth-grade algebra placement, placing previously average- and low-performing students in algebra can potentially undermine their motivation for mathematics.